Ideological aspects of capitalism in Contemporary Society: A critical analysis on the discursive field of politics - Nadir Lara Junior (Universidade do Vale do Rio dos Sinos (UNISINOS), 2016)
This article presents key aspects of ideological conflicts that take place in the discursive field of politics. It is the field where strategies of ideological domination of the ruling classes over the others come up. Also, there appear in that field ideological strategies which call the subject of the unconscious to take a position other than the dominated one. For this purpose, we have referred to theoretical postulates of authors who have a theoretical commitment to articulate psychoanalysis and Marxism with a view to find both theoretical and practical stands about the present political issues. It has been found that the discursive field of politics may aid us to comprehend and dismantle ideological constructions which try to oppress workers even more. That field may also make it possible for subjects to organize and build a more efficient political project against the capitalist model.